Pengunaan Augmented Reality Dalam Pendidikan Yang Meningkatkan Motivasi dan Efisiensi Belajar - Kawang Utomo; Nur Anisa (Jurnal Kajian Ilmiah, 2025)
Augmented Reality (AR) is a technology that combines virtual information with the real world to generate text, 3D objects, music, video, etc, to create immersive situation. These days, AR is being used in many kinds of sectors, one of it is education. Implementation of AR in education gives students enhancement on the learning process, AR could project a 3D object that gives student new perspective about the subject on their learning and AR can give interaction for the learners while they are observing. This study is about looking at the motivation that AR could give and how efficient the AR that implemented in education. With this we will find out whether AR has a good impact on the education world.